Red jasmine rice extract suppresses genes associated with cartilage degradation in IL-1β-stimulated chondrosarcoma (SW1353) via blocking NF-κB pathway - Ongchai, Siriwan; Thonghoi, Supitcha; Jaitham, Rungnaree; Kongdang, Patiwat; Yodkeeree, Supachai; Ongchai, Siriwan; Limtrakul, Pornngarm (Biomedical Sciences and Clinical Medicine, 2018)
Objective This study aimed to evaluate the chondroprotective potential of red jasmine rice crude extract (RRE) against an expression of genes associated with cartilage degradation stimulated by IL-1β in a human chondrosarcoma cell line, SW1353, culture model. Methods SW1353 cells were pre-incubated with 1 ng/mL of recombinant human interleukin-1β (IL-1β) followed by the addition of RRE in a range of concentrations from of 0 to 100 µg/mL. After 24 hours of incubation, cells were harvested and expression of genes associated with cartilage degradation was measured using real-time RT-PCR. The culture media were evaluated for MMP-13 levels using an ELISA kit. Upregulation of the signaling pathway which promotes the inflammatory cascade, nuclear factor kappa B (NF-κB), was determined by Western blot analysis. Results Cytokine IL-1β significantly upregulated the expression of the proinflammatory mediators IL-1β, IL-6, TNF-α, and COX-2 as well as enzymes involved in osteoarthritis such as MMP-13, ADAMTS-4, and ZIP-8. The results showed that RRE at a concentration of 100 µg/mL significantly suppressed IL-1β-induced expression of these genes. Moreover, the effect of IL-1β on NF-κB signaling pathway activation was suppressed by RRE via decreased phosphorylated form of IKKα/β, IκBα, and NF-κB p65. Conclusion RRE has chondroprotective potential through reduction of the gene upregulating effect of IL-1β which involve cartilage degradation via suppression of the NF-κB signaling pathway. Development of RRE has for alternative use potential in treating degenerative joint diseases.